Human Carotid Artery Smooth Muscle Cells Rarely Express αvβ3 Integrin at Sites of Recent Plaque Rupture - Ikari, Yuji; Yee, Karen O.; Hatsukami, Thomas S.; Schwartz, Stephen M. (Thrombosis and Haemostasis, 2000)
Fibrin(ogen) is the major matrix ligand for β3 integrins. If αvβ3 is the major receptor for fibrin(ogen) on intimal smooth muscle cells, we might expect to see this integrin associated with fibrin(ogen). Eightyfour specimens obtained from endarterectomies of 14 patients were studied. Fibrin was frequently observed in carotid intima even at the non-atherosclerotic areas. As for β1 and β3 integrins, β1 was predominant in intima. The αvβ3 integrin expression was less frequent than α5β1, another receptor for fibrin(ogen), in diffuse intimal thickening, fibrous cap and advanced plaques. Furthermore, αvβ3 was generally negative on smooth muscle cells in recent plaque ruptures. In conclusion, we suggest more attention should be paid on abundant fibrin matrix in intima. Histologically, the α5β1 integrin rather than the αvβ3 is the major receptor for fibrin in intimal smooth muscle cells.
Keywords: Fibrin; fibrinogen; tissue factor; immunohistochemistry; carotid endarterectomy